Structural, optical, and conductive properties of a poly(styrene)‐b‐poly(thiophene) copolymer doped with fullerenes under different conditions. Issue 7 (1st November 2013) - Politakos, Nikolaos; Grana, Eftychia; Zalakain, Iñaki; Katsigiannopoulos, Dimitrios; Eceiza, Arantxa; Kortaberria, Galder; Avgeropoulos, Apostolos
Abstract In this manuscript mixtures of a poly(styrene)‐b‐poly(thiophene) (PS‐b‐PT) copolymer with fullerenes (C60) as a dopant were prepared in order to evaluate their optical/surface properties through optical microscopy (OM) and atomic force microscopy (AFM) measurements respectively, as well as their conductivity through the four probe technique under variable conditions such as: temperature (room temperature and 150°C), solvent (toluene and chlorobenzene) and dopant concentration (2 and 5 wt %). The results exhibited that thermal treatment; solvent polarity and dopant concentration influence significantly the optical absorbance values. Ultraviolet‐visible spectroscopy (UV‐Vis) was also adopted to examine the optical absorbance of the mixtures and how it can be affected by the structures obtained in each case. The results for the variables involved in this study were very interesting and led to significant conclusions concerning the potential application of the proposed mixture for improved organic solar cells. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40084.